2016
DOI: 10.1136/bjsports-2016-095973
|View full text |Cite
|
Sign up to set email alerts
|

Training load--injury paradox: is greater preseason participation associated with lower in-season injury risk in elite rugby league players?

Abstract: Maximising participation in preseason training may protect elite rugby league players against in-season injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
110
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(113 citation statements)
references
References 29 publications
0
110
2
1
Order By: Relevance
“…27,41,54,[74][75][76][77] Collectively, these results suggest that training load might best be described as the "vehicle" that drives athletes toward or away from injury. 78 In the first study to demonstrate the protective effect of high training loads, Hulin et al 74 reported that cricket fast bowlers who bowled a greater number of balls over a 4-week period (ie, chronic training load) had a lower risk of injury than bowlers who bowled fewer balls. These findings have subsequently been replicated across a wide range of sports (eg, rugby league, Australian football, Gaelic football) and have given rise to the ACWR (previously referred to as training-stress balance) 76 (size of current training load relative to chronic).…”
Section: Athlete-load Monitoring and Injury Preventionmentioning
confidence: 99%
“…27,41,54,[74][75][76][77] Collectively, these results suggest that training load might best be described as the "vehicle" that drives athletes toward or away from injury. 78 In the first study to demonstrate the protective effect of high training loads, Hulin et al 74 reported that cricket fast bowlers who bowled a greater number of balls over a 4-week period (ie, chronic training load) had a lower risk of injury than bowlers who bowled fewer balls. These findings have subsequently been replicated across a wide range of sports (eg, rugby league, Australian football, Gaelic football) and have given rise to the ACWR (previously referred to as training-stress balance) 76 (size of current training load relative to chronic).…”
Section: Athlete-load Monitoring and Injury Preventionmentioning
confidence: 99%
“…However, they also demonstrated that as long as acute:chronic workload ratios were kept within a moderate zone (0.85–1.35), high chronic workloads were associated with the lowest risks of injuries, other than in the case of players with very low (<2 SD) acute:chronic ratios (table 2). 13 In a subsequent rugby league study, the odds of sustaining an injury during the competitive season were decreased by 17% for every 10 preseason sessions that players completed, controlling for in-season workloads 67…”
Section: Workloads and Injuries—what Do We Know?mentioning
confidence: 99%
“…Findings conflicted. Hulin et al 1 demonstrated that acute:chronic workload ratios >1.5 were associated with injury, while Windt et al 6 did not find that relationship. However, Hulin et al 1 considered an injury to be ‘any time-loss injury that resulted in a player being unable to complete full training or missing match time’; Windt et al 6 investigated injuries that resulted in ‘match time loss only’.…”
Section: We Should Not Overlook Injury Definitionmentioning
confidence: 99%
“…Hulin et al 1 demonstrated that acute:chronic workload ratios >1.5 were associated with injury, while Windt et al 6 did not find that relationship. However, Hulin et al 1 considered an injury to be ‘any time-loss injury that resulted in a player being unable to complete full training or missing match time’; Windt et al 6 investigated injuries that resulted in ‘match time loss only’. Please note that previous workload-injury studies have included a broader injury definition that encompasses ‘any pain or disability suffered by a player during a match or training session and subsequently assessed during or immediately after the match or training session’ (ie, ‘medical attention injuries’) 7…”
Section: We Should Not Overlook Injury Definitionmentioning
confidence: 99%
See 1 more Smart Citation